Risk factors associated with post-therapeutic outcome for medulloblastoma: An experience from Indonesia - Tandian, David; Harlyjoy, Alphadenti; Nugroho, Setyo; Ichwan, Syaiful (Asian Journal of Neurosurgery, 2021)
Context: The prognosis of medulloblastoma is better in patients who underwent complete treatment consisting of surgery, radiotherapy, and chemotherapy. However, the realization of such multidiscipline management is quite challenging in developing countries, including Indonesia. Until now, no study on the management of medulloblastoma has ever been conducted in Indonesia. Aims: The authors aimed to study the characteristics, management, and mortality outcome of medulloblastoma patients in Dr. Cipto Mangunkusumo National Referral Hospital, Jakarta, Indonesia. Subjects and Methods: This study was based on medical record and registry of 44 medulloblastoma patients who underwent tumor removal in Dr. Cipto Mangunkusumo National Referral Hospital, Jakarta, Indonesia, between 2011 and 2018. Statistical Analysis Used: Cox regression analysis was utilized to determine the relationship between patients' demography, tumor characteristics, and treatment, with mortality. Results: The incidence of mortality was 84.1% and median months' survival time (95% confidence interval [CI]) was 13 (8.67–17.32). Gross total removal (GTR) was performed in 43.2% of all tumor removal surgery. Only 50% of all patients completed radiotherapy, and 6.8% concluded multimodalities treatment (surgery, radiotherapy, and chemotherapy). Significant statistical association between age, gender, and extent of resection with mortality was identified (HR [95% CI] for age: 0.44 [0.22–0.88], gender: 0.001 [0.000–0.27; REF: female], and biopsy: 31.52 [1.09–910.56; REF: GTR]). Conclusions: The survival rate of medulloblastoma in Indonesia is inferior to that previously reported in other studies. There is no unusual characteristic contributing to neoteric risk factor. The authors surmise that insufficient multidisciplinary management for the disease, consisting of suboptimal tumor resection, the absence of risk stratification, and incomplete postsurgical treatment (radiotherapy and chemotherapy) resulted in such outcome.
Keywords: Age; extent of resection; gender; medulloblastoma; mortality